2010
DOI: 10.1007/s00406-010-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of soluble TNF receptor I in patients with bipolar disorder

Abstract: Bipolar disorder (BD) has been associated with a proinflammatory state in which TNF-α seems to play a relevant role. The aim of the present study was to evaluate the plasma levels of TNF-α and its soluble receptors (sTNFR1 and sTNFR2) in BD patients in mania and euthymia in comparison with control subjects. We evaluated 53 BD patients (34 in mania and 19 in euthymia) and 38 healthy subjects. All subjects were assessed by the Mini-International Neuropsychiatry Interview (MINI-Plus). Patients were also evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 25 publications
4
87
1
5
Order By: Relevance
“…It was shown that serum soluble IL-2 receptor, interferon-γ, and serum tumour necrosis factor (TNF)-α receptor 1 levels were increased in manic patients compared to euthymic patients and healthy controls [4,10,11]. Additionally, IL-6, TNF-α, and soluble IL-2 receptor were reported to be significantly increased in manic episodes compared to healthy controls [5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that serum soluble IL-2 receptor, interferon-γ, and serum tumour necrosis factor (TNF)-α receptor 1 levels were increased in manic patients compared to euthymic patients and healthy controls [4,10,11]. Additionally, IL-6, TNF-α, and soluble IL-2 receptor were reported to be significantly increased in manic episodes compared to healthy controls [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…The biological mechanisms of BD still remain unclear, but it can be effectively conceptualized as a multi-systemic inflammatory disease [3]. To date, changes in peripheral inflammatory markers have been reported in BD such as cytokine profiles [4][5][6][7][8][9][10][11], acute phase proteins [12][13][14], and lymphocyte cell activation [5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Iako dve studije Barbosa i sar. (2010, 2012) [36,41] govore o povećanim nivoima BDNF u kasnijim fazama bolesti, metaanalize nalaze sniženje BDNF u okviru akutne epizode, ali ne i eutimije, koje korelira sa starošću i dužinom bolesti. Istovremeno, sniženje nivoa neurotrofnih faktora, često je praćeno i poveća-njem parametara oksidativnog stresa što govori u prilog značajnog medjuodnosa neuroprotektivnih, inflamatornih i oksidativnih mehanizama u etiopatogenezi BAP [24].…”
Section: Neurotrofiniunclassified
“…[63][64][65] Nevertheless, these findings may be less specific, since significant changes in these cascades have also been observed in other neuropsychiatric and neurodegenerative conditions, such as major depression, bipolar disorder, schizophrenia, and Parkinson's disease. [66][67][68][69][70][71] Blood cells, namely leukocytes and platelets, may also be an important source of AD-related biomarkers, since they can provide insights on the systemic modulation of biological cascades that are supposedly altered in AD. For instance, platelets represent the most important source of circulating APP, and the regulatory loops of peripheral APP metabolism seem to parallel intracerebral homeostasis.…”
Section: Peripheral Biomarkersmentioning
confidence: 99%